A Legal Analysis of The Practice of Review Manipulation (Fake Reviews) on Marketplaces as A Form of Unfair Business Competition in Indonesia - Raihan Muhammad Maliki; Muhammad Fahmi Ramdhani; Syifa Walidatunnisa; Muhammad Habib Al badawy; Najda Inayah Nurfadiah; Muhammad Alhikam Badruttamam; Arzhety Ityana Kamalia Mukhlis; Nandang Najmudin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legal status of review manipulation practices in digital marketplaces and evaluates their qualification as a form of unfair business competition within the Indonesian legal framework. Employing a non empirical legal research design with a normative juridical approach, the study analyzes statutory regulations, legal doctrines, and conceptual principles related to competition law, consumer protection, electronic transactions, and criminal law. The findings indicate that fake reviews constitute a deceptive mechanism that distorts market transparency and creates artificial competitive advantages that are inconsistent with the principles of fair competition. Although Indonesian Competition Law does not explicitly regulate fake reviews, systematic and teleological interpretation demonstrates that such practices contradict the objectives of maintaining equal market opportunities and protecting competitive neutrality. The analysis further reveals significant regulatory fragmentation among consumer protection, electronic transaction, and criminal law regimes, resulting in enforcement difficulties and legal uncertainty. Comparative examination of foreign regulatory developments suggests the importance of strengthening marketplace accountability, establishing mandatory review verification systems, improving digital evidence standards, and expanding institutional oversight. Legal reform is therefore necessary to ensure effective governance of digital marketplaces and preserve competitive integrity in Indonesia’s evolving digital economy.